A bacterial quorum sensing signal is a potent inhibitor of de novo pyrimidine biosynthesis in the globally abundant Emiliania huxleyi - Garrett, Oscar; Whalen, Kristen E. (Frontiers in Microbiology, 2023)
Interactions between marine phytoplankton, viruses, and bacteria drive biogeochemical cycling, shape marine trophic structures, and impact global climate. Microbially produced compounds have emerged as key players in influencing eukaryotic organismal physiology, and in turn, remodel microbial community structure. This work aimed to reveal the molecular mechanism by which the bacterial quorum sensing molecule 2-heptyl-4-quinolone (HHQ), produced by the marine gammaproteobacterium Pseudoalteromonas spp., arrests cell division and confers protection from virus-induced mortality in the bloom-forming coccolithophore Emiliania huxleyi. Previous work has established alkylquinolones as inhibitors of dihydroorotate dehydrogenase (DHODH), a fundamental enzyme catalyzing the fourth step in pyrimidine biosynthesis and a potential antiviral drug target. An N-terminally truncated version of E. huxleyi DHODH was heterologously expressed in E. coli, purified, and kinetically characterized. Here, we show HHQ is a potent inhibitor (Ki of 2.3 nM) of E. huxleyi DHODH. E. huxleyi cells exposed to brequinar, the canonical human DHODH inhibitor, experienced immediate, yet reversible cellular arrest, an effect which mirrors HHQ-induced cellular stasis previously observed. However, brequinar treatment lacked other notable effects observed in HHQ-exposed E. huxleyi including significant changes in cell size, chlorophyll fluorescence, and protection from virus-induced lysis, indicating HHQ has additional as yet undiscovered physiological targets. Together, these results suggest a novel and intricate role of bacterial quorum sensing molecules in tripartite interdomain interactions in marine ecosystems, opening new avenues for exploring the role of microbial chemical signaling in algal bloom regulation and host-pathogen dynamics.